Regulating Artificial Intelligence in Developing and Centralized Legal Systems: A Comparative Study of Indonesia and China - Christian Andersen; Shavilla Felisya Regitara (Journal of Social Research, 2026)
Artificial intelligence (AI) has developed rapidly and is increasingly integrated into various sectors, including public administration, finance, and digital platforms. However, the expansion of AI technologies also presents significant legal and regulatory challenges, particularly in developing legal systems where regulatory frameworks remain limited. This study examined AI regulation in Indonesia and China through a comparative legal analysis using a normative legal research method that analyzed legislation, policy documents, and academic literature related to AI governance. The findings indicated that Indonesia currently adopts a fragmented and policy-based regulatory approach, whereas China has established a more comprehensive and enforceable regulatory framework governing algorithmic systems and emerging AI technologies. The study also identified several regulatory gaps in Indonesia, including the absence of specific AI legislation, limited institutional coordination, and inadequate mechanisms for algorithmic accountability. Therefore, this research argues that Indonesia needs to develop a comprehensive and enforceable AI regulatory framework that integrates legal certainty, risk-based governance, and institutional coordination by drawing lessons from China’s regulatory experience while considering Indonesia’s legal and institutional context.